BEES ARE MESSENGERS: THE UNUSUAL AS A DEVICE FOR THE RELATIONSHIP BETWEEN RADICAL OTHERNESS IN MARGARET ATWOOD’S MADDADDÃO AND DANIEL GALERA’S BUGÔNIA (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2026)
The worsening of environmental crises and the collapse of exploitative anthropocentrism are driving a literature focused on the coexistence between humans and non-humans. This article analyzes the use of the unusual as a literary device in the construction of relationships between humans and bees in Margaret Atwood's O Ano do Dilúvio (2011) and MaddAddão (2019), and in Daniel Galera's short story Bugônia (2021), in light of critical posthumanism. It observes that bees cease to occupy a utilitarian role, integrating into communities based on communication, care, and relational survival, without fixed hierarchies. In this sense, the unusual destabilizes realistic pacts and challenges binaries such as human/animal and nature/culture. Furthermore, the protagonism of women as mediators of these bonds is highlighted, acting in the preservation of memory, care, and translation between worlds, contributing to the imagination of possible ethical futures in the face of environmental ruin.